Manejo populacional de cães e gatos: análise do controle reprodutivo em Belo Horizonte – Minas Gerais - José Honorato Begalli (2020)
The work aimed to analyse the strategy of mass reprodutctive control of domestic dogs and cats, focusing on the zoonosis and population control. In this regard, the purpose was: to analyse the impact of mass reproductive control of dogs in the zoonosis transmission to humans, through a systematic review; to analyse the reproductive control actions for the domiciled and not domiciled dogs and cats population regarding to gender, age, and Health Vulnerability Index of the place of residence; to analyse the effectiveness of the reproductive control strategy of domiciled and not domiciled dogs and cats, regarding the population growth of these species.It was verified that there is not enough evidence to state that the dogs mass sterilization as the only strategy can reduce human cases of zoonosis; there is a growing trend in the performed sterilizations and a trend of absenteeism in both species, about the scheduled animals, during the period, remaining 1 dog for 8 inhabitants, and 1 cat for each 25 inhabitants in 2018.The association between species and absenteeism was substantial, with a absenteeism risk 1,02 times bigger for the canine species’ tutors; tutors who are residents in Barreiro region presented the lowest risk of absenteeism, comparing to the average rate of absenteeism in the period.The regions with lower socioeconomic index in the municipality are the ones which have been showing the lowest access to the public service of castration; there is a bigger demand of collection for dogs comparing to cats during the whole period, and related to the gender, male dogs are collected the most, and with cats, the female ones have the biggest average of collection. The administrative region which had the biggest demand was the North, followed by Venda Nova, and the one with the lowest demand was the West. There is a necessity of more studies involving other factors of the population management.